The English Text Types Applied In English Textbooks For Students of Islamic Education Department - Ulva Fatiya Rosyida; Arif Ma'mun Rifa'i; Warsiyah Warsiyah (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2022)
This research aims at describing the English text types applied in English Textbooks for students of Islamic Education Department. The teaching must be relevant with the students’ needs and the purpose of language teaching. One of the purposes is for understanding the different text types. Moreover, the college students should be in epistemic level. In this level, they are expected to be able to use English in transforming knowledge. The findings reported that there are ten text types applied in the textbooks. The dominant text is Information Report while the least is News Item. Almost the materials contain information related to Islamic knowledge. It also integrates the knowledge of how to use language for different purposes and functions, how to produce and understand different text types, and what the common linguistic features of each text type.